The effects of a novel invasive predator (Rhithropanopeus harrisii) on rocky littoral invertebrate community in the Northern Baltic - Nousiainen, Eino (My University, 2026)
Human facilitated introductions of invasive species into aquatic systems on a global scale result in major environmental and economic losses. Many contemporary examples have shown that invasive species have the ability to drive native population to extinction. Invasive predators can cause major disturbances to native communities through either direct (competition, predation) or indirect (interaction chains or interaction modification) means. In the Northern Baltic Sea, prior studies have suggested that a novel invasive decapod, Rhithropanopeus harrisii, can drastically reduce important mesoherbivore densities in rocky littoral habitats. In this thesis, I investigated changes in invertebrate communities exposed to R. harrisii in Fucus vesiculosus dominated shores. I compared community structures and the abundance of affected species across sites with different durations of crab exposure. Results suggested that R. harrisii can quickly decimate much of the native mesoherbivore community. In their place, densities of filter feeders and bivalves increased. Even sites with long co-existence with the crab did not show signs of recovery, possibly due to delayed prey antipredatory responses or a more persistent regime shift enforced by the crab. I argue that the changes to invertebrate communities and release from top-down control for macrophytes can likely worsen growth conditions for slow-growing perennial algae and exacerbate eutrophication-like effects as a result of reduced herbivory.
Keywords: community ecology, aquatic ecology, invasive species, Baltic Sea